Revitalisasi Nilai Kebajikan Kewarganegaraan Berbasis Kearifan Lokal melalui Tradisi Perang Timbung Desa Pejanggik - M. Khairul Hafiz Jauhari; Nasiwan Nasiwan (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
Indonesia's rich cultural heritage contains numerous local traditions steeped in virtue, yet many face the threat of degradation due to modernization. The Timbung War tradition in Pejanggik Village, Central Lombok, represents an important local wisdom that has not been comprehensively studied as a means of preserving virtue. This study aims to analyze its multidimensional meaning, identify virtue values, and describe its role in strengthening social cohesion within the community. The method used was a qualitative ethnographic approach through in-depth interviews, participant observation, and documentation of traditional leaders, religious leaders, village government officials, and the younger generation. Data analysis included data condensation, data presentation, and drawing conclusions. The results indicate: (1) the tradition serves as a meaningful ritual of gratitude, a medium for fostering friendship, and a means of conflict resolution; (2) six virtue values are embodied: mutual cooperation, togetherness, spirituality, courtesy, social awareness, and responsibility; (3) the tradition effectively preserves values through sangkep agung and the involvement of the younger generation, although some youth interpret it ceremonially. This study confirms its potential as an instrument for character education based on local wisdom.